A Case Series of Ketoacidosis After Coronavirus Disease 2019 Vaccination in Patients With Type 1 Diabetes - Yakou, Fumiyoshi; Saburi, Masuo; Hirose, Ai; Akaoka, Hiroaki; Hirota, Yusuke; Kobayashi, Takaaki; Awane, Naoko; Asahi, Nobuteru; Amagawa, Toshihiro; Ozawa, Sachihiko; Ohno, Atsushi; Matsushita, Takaya (Frontiers in Endocrinology, 2022)
Introduction: We report a case series of severe ketoacidosis after COVID-19 vaccination in a type 1 diabetes patients treated with insulin and an SGLT-2 inhibitor. Case Report: We present two cases of type 1 diabetes mellitus. One patient was treated with insulin therapy and an SGLT-2 inhibitor, and the was treated with insulin therapy alone. Both patients became ill after coronavirus disease-2019 vaccination, making it difficult to continue their diet or insulin injections. On admission, they developed severe diabetic ketoacidosis. This is the first report of ketoacidosis after coronavirus disease-2019 vaccination. Conclusion: The vaccine should be carefully administered to type 1 diabetes patients receiving intensive insulin therapy and a sodium-glucose transporter due to the high risk ketoacidosis. It is important to instruct patients to drink sufficient fluids and to continue insulin injections when they become sick.